2022
DOI: 10.1039/d1ee03673d
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric wide-bandgap acceptor simultaneously enabling highly efficient single-junction and tandem organic solar cells

Abstract: The ternary and tandem strategies are effective methods for improving the photovoltaic performance of organic solar cells (OSCs). Here an asymmetric wide-bandgap nonfullerene acceptor named AITC is synthesized. AITC with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 43 publications
0
81
0
Order By: Relevance
“…Among the device engineering approaches, the ternary-component strategy has become the most popular topic in recent years. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Pursuing favorable morphological evolution in ternary systems is at the core of optimizing new OSC materials towards excellent performances. Consequently, one of the main goals of OSC research is to determine the morphology tuning effect of the ternary-component strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the device engineering approaches, the ternary-component strategy has become the most popular topic in recent years. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Pursuing favorable morphological evolution in ternary systems is at the core of optimizing new OSC materials towards excellent performances. Consequently, one of the main goals of OSC research is to determine the morphology tuning effect of the ternary-component strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] In recent years, the emergence and stunning rise of ITIC‐ and Y‐series non‐fullerene acceptors, as well as a subtly device engineering, have boosted the power conversion efficiency (PCE) to a new breakthrough. Currently, the PCE of a single‐junction OSCs has reached 19% [ 4,5 ] and that of a tandem device is more than 20%. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Zhang et al reported the lower non-radiative voltage of ternary OSCs by incorporating an asymmetric medium bandgap (1.75 eV) acceptor AITC on the basics of 3,9-bis(2-methylene(3-(1,1dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2 0 ,3 0 -d 0 ]-s-indaceno[1,2-b:5,6-b 0 ]dithiophene (ITIC) derivatives 16 as the third component in the PM6:BTP-eC9 system, contributing to the improved open-circuit voltage (V oc ) of OSCs. 37 Zhu et al designed a Y6 analogue, AQx-3, and introduced it into the PM6:Y6 binary system, and over 18% PCE improvement was realized in the optimized ternary OSCs relatively beneting from the alloy-like composites formed by two acceptors with superior lm morphology. 38 Hence, the rational choice of the guest acceptor plays a key role in promoting the ternary device performance.…”
Section: Introductionmentioning
confidence: 99%